2018
DOI: 10.2478/foecol-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Traffic effects on leaf macro- and micro-morphological traits

Abstract: The aim of this study was to evaluate the traffic-related effects on morphological and anatomical traits of Fraxinus rotundifolia and Morus alba along the Malayer-Hamedan road. In the study area, populations of two species of F. rotundifolia (30 individual trees) and M. alba (30 individual trees) were selected for sampling. The results showed that the leaf and stomata dimensions at distances near to the roadside were significantly lower compared to longer distances from the road. For F. rotundifolia, the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
3
0
2
Order By: Relevance
“…According to the coefficient of correlation, LA is correlated with LW and PL. The different kinds of correlation among different leaf traits in beech (Bayramzadeh et al, 2008) and other species were also reported by other authors (Yousefzadeh et al, 2010, Rakonjac et al, 2014Allahnouri et al, 2018). The high heritability indicated that the effect of genotype is more important than the environmental pressures.…”
Section: Discussionsupporting
confidence: 61%
“…According to the coefficient of correlation, LA is correlated with LW and PL. The different kinds of correlation among different leaf traits in beech (Bayramzadeh et al, 2008) and other species were also reported by other authors (Yousefzadeh et al, 2010, Rakonjac et al, 2014Allahnouri et al, 2018). The high heritability indicated that the effect of genotype is more important than the environmental pressures.…”
Section: Discussionsupporting
confidence: 61%
“…The central cylinder has a well-developed mechanical tissue-the sclerenchyma (5). Cells with thick cell walls that lie in several layers (4)(5). The xylem vessels (6) are quite small, tracheids are rare, wood fibers are thick-walled.…”
Section: Resultsmentioning
confidence: 99%
“…International Journal of Biology and Chemistry 14, № 1, 141 (2021) which consumes less water, so it is suggested when choosing urban landscaping tree species [2]. The inclusion of ash species in the urban catalog of tree species for the description and identification of harmful substances caused by pollution makes it possible to identify the environmental crisis in cities and megacities in the short and medium term [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they point to the importance of considering changes at the whole plant level, since the energetic demands on individual tissues are likely different and therefore the tradeoff between development and defence (success) plays a significant role. Because of the natural variability in not only aperture (dynamics) but also cell features of leaf epidermis (stomata), the nature and efficiencies of responses to (metal) stress are probably highly complex and are relevant not only for metal uptake by roots but even more by stomata [6,57].…”
Section: Discussionmentioning
confidence: 99%